Understanding Keloid Pathobiology From a Quasi-Neoplastic Perspective: Less of a Scar and More of a Chronic Inflammatory Disease With Cancer-Like Tendencies - Tan, Silvian; Khumalo, Nonhlanhla; Bayat, Ardeshir (Frontiers in Immunology, 2019)
Keloids are considered as benign fibroproliferative skin tumors growing beyond the site of the original dermal injury. Although traditionally viewed as a form of skin scarring, keloids display many cancer-like characteristics such as progressive uncontrolled growth, lack of spontaneous regression and extremely high rates of recurrence. Phenotypically, keloids are consistent with non-malignant dermal tumors that are due to the excessive overproduction of collagen which never metastasize. Within the remit of keloid pathobiology, there is increasing evidence for the various interplay of neoplastic-promoting and suppressing factors, which may explain its aggressive clinical behavior. Amongst the most compelling parallels between keloids and cancer are their shared cellular bioenergetics, epigenetic methylation profiles and epithelial-to-mesenchymal transition amongst other disease biological (genotypic and phenotypic) behaviors. This review explores the quasi-neoplastic or cancer-like properties of keloids and highlights areas for future study.